Analisis Keterlibatan Masyarakat dalam Mengembangkan Air Terjun Bidadari Sebagai Pariwisata Berkelanjutan Berbasis Masyarakat di Kabupaten Lahat - Geri Ronaldo; Purwati Purwati; Desloehal Djumrianti (Politeknik Negeri Sriwijaya, 2022)
This study aims to make Bidadari Waterfall Tourism Object community-based sustainable tourism in Lahat Regency. This study uses a qualitative-descriptive research method with data collection techniques in the form of interviews, questionnaires, and documentation. The analysis technique in this research is the SWOT analysis. The results of this study obtained a total internal factor of 1.23 and an external factor of 1.29 which means an aggressive policy (growth-oriented strategy). Thus, obtaining four sets of strategies that can be applied to the Bidadari Waterfall Tourism Object includes Sustainable Economy: The quality of the tourism products offered by the community/managers such as rock climbing on the Bidadari Waterfall Wall to attract tourists and Cooperation between the community and managers to become tour guides to increase the income of the local community and managers. Sustainable Social: The polite attitude of the community to show hospitality to tourists visiting Bidadari Waterfall and residents who use local languages ​​can maintain the culture and traditions of Karang Dalam Village. Sustainable Environment: People who maintain biodiversity can maintain their ecosystem to attract tourists. Thus, managers and the community must work together with the local government to develop Bidadari Waterfall Tourism Object as sustainable tourism in Lahat Regency based on the dimensions of sustainable economic, socially sustainable, and environmentally sustainable tourism.